Influence of glucose concentration on the structure and quantity of biofilms formed by Candida parapsilosis - Pereira, Leonel (2015)
Candida parapsilosis is nowadays an emerging opportunistic pathogen and its increasing incidence is part related to the capacity to produce biofilm. In addition, one of the most important C. parapsilosis pathogenic risk factors includes the organisms’ selective growth capabilities in hyper alimentation solutions. Thus, in this study, we investigated the role of glucose in C. parapsilosis biofilm modulation, by studying biofilm formation, matrix composition and structure. Moreover, the expression of biofilm-related genes (BCR1, FKS1 and OLE1) were analyzed in the presence of different glucose percentages. The results demonstrated the importance of glucose in the modulation of C. parapsilosis biofilm. The concentration of glucose had direct implications on the C. parapsilosis transition of yeast cells to pseudohyphae. Additionally, it was demonstrated that biofilm related genes BCR1, FKS1 and OLE1 are involved in biofilm modulation by glucose. The mechanism by which glucose enhances biofilm formation is not fully understood, however with this study we were able to demonstrate that C. parapsilosis respond to stress conditions caused by elevated levels of glucose by up-regulating genes related to biofilm formation (BCR1, FKS1 and OLE1).